PROFIL PARA GAMERS DI KOTA PEKANBARU (STUDI TENTANG PERUBAHAN SOSIAL PENGGEMAR GAME ONLINE DI WARNET MARKAS NET Jl. DURIAN, PEKANBARU) - Jorgi Andrie Flageo; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background of this study by the increasingly widespread phenomenon ofincreasingly rapid internet cafes in the city of Pekanbaru. Not only that difungsingkan internetcafes all websites visited by users for general but specific internet cafes online games or gamingcenter that can be said is also growing rapidly, game center is a cafe that is only reserved foronline gaming enthusiasts or for those who like to play online games. Not only that game centercan open all the sites. Now there are 119 internet cafes are open 24 hours have been scatteredthroughout the region in Pekanbaru, and one of them on the road Durian. On the road there areinternet cafes named Markas Net. The form of this research is qualitative with purposivesampling as a sampling technique, which can describe thoroughly how profiles online gamingenthusiasts often called gamers, ranging from gamers identity, gender, age, education, behavior,until the work of parents, and revenue parents and impact derived from playing online games.Then, the results of this study indicate that most who play online games are men than womenwho do not like noise. Later, age and education are also strongly associated with online gamesthey play. As well, the pocket money they get often can not determine whether or not they playonline games. The number of online games that exist in Markas Net with the number of 34online games, but from this study found four very popular online game played dansering gamersat Markas Net, namely Dragon Nest, Dota 2, Lost Saga and Point Blank (PB).Keywords: Profile Gamers, Headquarters Net, Game Centre, Games Online